circRNAs: Insight Into Their Role in Tumor-Associated Macrophages - Duan, Saili; Wang, Shan; Huang, Tao; Wang, Junpu; Yuan, Xiaoqing (Frontiers in Oncology, 2021)
Currently, it is well known that tumor microenvironment not only provides energy support for tumor growth, but also regulates tumor signaling pathways and promotes proliferation, invasion, metastasis and drug resistance of tumor cells. Tumor microenvironment, especially the function and mechanism of tumor-associated macrophages (TAMs) has attracted great attention. TAMs are the most common immune cells in the tumor microenvironment and play a vital role in the occurrence and development of tumors. Circule RNA (CircRNA) is a unique, widespread and stable form of non-coding RNAs (ncRNAs), but little is known about the role of circRNAs in TAMs and how TAMs act on circRNAs. In this review, we summarized the specific manifestations of circRNAs affecting the tumor-associated macrophages, and play a significant role in the tumor progression. To improve our understanding of the association between circRNAs and TAMs, so as to promote the development and progress of potential clinical targeted therapy.